PENGGUNAAN TEORI SIGNALING DALAM PENELITIAN AKUNTANSI DAN KEUANGAN: STUDI LITERATURE REVIEW - Hendy Satria; Natasya Saffa Adesti; Raja Fitriana; Rani Sofia Magdalena; Sekar Melati; Suci Alya Rahmadhani (KAMPUS AKADEMIK PUBLISING, 2026)
Signaling Theory is a widely used theoretical foundation in accounting and finance research to explain the mechanisms by which companies convey information to stakeholders under conditions of information asymmetry. This study aims to analyze the development of Signaling Theory's use in accounting and finance research and identify dominant research themes and future research opportunities. The study employed a literature review method, analyzing various sources discussing Signaling Theory. The analysis process involved identifying, classifying, evaluating, and synthesizing literature addressing the application of Signaling Theory in accounting and finance. The study's results indicate that Signaling Theory is widely used in research on corporate information disclosure, financial statements, dividend policy, capital structure, earnings quality, and firm value. Furthermore, developments in the business environment have expanded the theory's use to address contemporary issues such as Environmental, Social, and Governance (ESG), corporate social responsibility (CSR), and sustainability reporting. The research findings demonstrate that Signaling Theory remains relevant in explaining various forms of corporate communication, both financial and non-financial. This study contributes by mapping the development of Signaling Theory's use and recommending possible future research directions.